TINGKAT PERSAINGAN DAN EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA - Afrianty, Nonie; Anto, Moh. Bekti Hendrie (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Abstract : The development of sharia banking in Indonesia can not be separated from its important role as an intermediary institution as well as developing the economy by channeling funds for productive businesses, especially middle, small and micro entrepreneurs. Sharia banking that has a strategic role in funding for micro business is one of them is the Sharia Rural Bank (BPRS). Therefore, BPRS must operate efficiently to promote economic growth and competitiveness so as to survive in the face of tight financial industry competition in Indonesia. This research is conducted to analyze the level of competition / competition and efficiency of Sharia Rural Bank (BPRS) in Indonesia. The data used in this research is the financial report of 113 BPRS in Indonesia obtained from Bank Indonesia. The methods used to analyze the level of competition are Herfindahl-Hirschman Index (HHI) and Concentration Ratio (CR). The analysis of this level of competition includes three variables, including assets, Third Party Funds (DPK) and Financing. While the methods used to analyze the level of efficiency include two input variables and three output variables, including DPK, Operational Costs, Financing Disbursed, Current Assets and Other Operating Income.Analisis of BPRS competition level in Indonesia in 2011-2015 shows that BPRS in Indonesia tend to experience competition or competition between BPRS and not controlled by several BPRS. While at the level of efficiency of BPRS in Indonesia 2011-2015 using Data Envelopment Analysis (DEA) approach resulted 5 (five) BPRS with efficiency value 1 or 100%. In addition, for SRBs in inefficient conditions the DEA method also provides a reference or reference in order to be able to achieve efficient conditions.Keywords: Competition, HHI and CR, Efficiency, DEA, SR